Knowledge of Nurses regarding Glasgow Coma Scale in Neurological Assessment of Patients in a Tertiary Care Hospital Multan - Ali, Sidra Ahmad; Rafique, Shaheen; Nawaz, Ali (Annals of Human and Social Sciences, 2024)
The objective of this study was to assess the knowledge of nurses regarding Glasgow Coma Scale in neurological assessment of patients in a Tertiary Care Hospital Multan. Neurological assessment is a fundamental aspect of patient care, the level of consciousness in patients with brain injuries has to assess with Glasgow Coma Scale. Descriptive cross sectional study design was used to carry out at Nishtar Hospital Multan. The sample size was 80 nurses. Convenient sampling method was used to collect the data. The results showed that 25 (28%) nurses demonstrated poor knowledge of the GCS, while 35 nurses (46%) exhibited an average level of understanding and 20 nurses (25%) showcased a good understanding of the GCS. In term of association, age groups show no significant association with knowledge levels. While gender, qualification, experience, and department of work exhibit significant associations with knowledge. Implement regular training sessions for nurses on the Glasgow Coma Scale.